Post-transplant Diabetes Mellitus (PTDM), a Retrospective Review Studying the Effect of Early Steroid Withdrawal in Libyan Recipients - Shebani, Abdulhafid A.; Marwan, Mohamed B.; Tabagh, Refaat M. (The Libyan Journal of Science, 2022)
Post-transplant diabetes mellitus (PTDM) is the most, and, frequent complication observed following solid organ transplantation. PTDM or the Kidney transplant recipients develop are also at increased risk of cardiovascular events and other adverse outcomes including infection, reduced patient survival, graft rejection, and accelerated graft loss compared with non-diabetics. In general new onset of diabetes mellitus after transplantation has been reported to occur in 4% to 25% of renal transplant recipients, 2.5% to 25% of liver transplant recipients, and approximately 2% to 53% of all people. 230 renal transplant recipients with functioning grafts were used in this study. This study took about 5 years in order to screen the incidences of PTDM and other risk factors. The aim is to study the incidence of new-onset of diabetes mellitus in kidney transplant recipients and correlate it with protocol of withdrawing steroids after one month after transplantation. The results confirm the importance of corticosteroids in the development of post transplantation new onset of diabetes mellitus in Libyan population. The data indicates that Libyan male patients are more vulnerable to PTDM than Libyan female patients.